2016
DOI: 10.1186/s12888-016-0879-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term health-related quality of life improvements among patients treated with lurasidone: results from the open-label extension of a switch trial in schizophrenia

Abstract: BackgroundLong-term improvement of health-related quality of life (HRQoL) in schizophrenia may improve adherence and reduce relapse and rehospitalization. This analysis examines long-term changes in HRQoL among patients with schizophrenia switched to lurasidone from other antipsychotics.MethodsPatients who completed an open-label 6-week switch study continued on lurasidone for an additional 24-weeks. HRQoL was measured using the self-reported Personal Evaluation of Transitions in Treatment (PETiT) scale and Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 74 publications
(80 reference statements)
0
7
1
Order By: Relevance
“…Studies examining quality-of-life improvements among persons with schizophrenia treated with lurasidone have been published. 40 , 41 In a 24-week extension 32 of an open-label 6-week switch study, 42 health-related quality of life was measured using the self-reported Personal Evaluation of Transitions in Treatment scale and Short-Form 12 questionnaire; improvements were observed on both of these measures, including components assessing adherence-related attitude and psychosocial functioning. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Studies examining quality-of-life improvements among persons with schizophrenia treated with lurasidone have been published. 40 , 41 In a 24-week extension 32 of an open-label 6-week switch study, 42 health-related quality of life was measured using the self-reported Personal Evaluation of Transitions in Treatment scale and Short-Form 12 questionnaire; improvements were observed on both of these measures, including components assessing adherence-related attitude and psychosocial functioning. 41 …”
Section: Discussionmentioning
confidence: 99%
“…It has an introductory aspect which outlines the purpose of the questionnaire and the need to consider their health in the last 1 week and a choice of one of three response (‘often’, ‘sometimes’ or ‘never’). 4 , 10 , 15 …”
Section: Methodsmentioning
confidence: 99%
“…Total scores are derived from the summation of the individual items and the authors ensured that attention was given to exclude any cultural and health-services related items, so that the scale could be used in a variety of health care facilities. 4 , 10 , 15 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations